THE STRATEGY OF TRANS TV'S INSERT PROGRAM IN BUILDING A POSITIVE IMAGE - Widya Tamara Sitohang; Wahyudi Marhaen Pratopo (Jurnal Komunikasi & Media Digital, 2025)
This study explains the strategy of adding the lifestyle segment to build a positive image of Trans TV’s Insert Program. Drawing on program production strategies, this study emphasizes the importance of initial research, proper implementation, and continuous evaluation in content planning and production. This research used a descriptive qualitative method by obtaining data through interviews, observations, and document study. The results of this study reveal the planning within the production team to understand audience preferences and the latest trends, which then translates into relevant and interesting content, especially in the lifestyle segment. Effective planning of the production and the diversity of content, such as make-up, fashion, and culinary, maintains the high quality and attractiveness of Trans TV’s Insert Program in building its positive image. Continuous evaluation ensures that every piece of content is always improved and adjusted to viewers' expectations. The results of this study provide important insights into television planning and production strategies, as well as practical contributions to the development of television programs in the future.